Integrating system dynamics and multicriteria analysis: towards organisational learning for performance improvement - Santos, Sérgio Pereira dos (2014)
The design, implementation and use of adequate performance measurement and management frameworks can play an important role if organizations are to succeed in an increasingly complex, interdependent and changing world. Yet, despite widespread recognition of the importance of performance assessment, there are some issues which require further study if measurement systems are to be effective in supporting the decision making process. This article argues that the integration between System Dynamics and Multicriteria Decision Analysis can address some of these issues, and ultimately contribute to improve organisational performance. To support this claim, several problems that make performance measurement systems fall short of their potential are outlined and, a discussion about how the integration of system dynamics and multicriteria analysis can help organisations overcome these problems is presented.